Echocardiography during preload stress for evaluation of right ventricular contractile reserve and exercise capacity in pulmonary hypertension. Issue 12 (16th October 2018) - Sano, Hiroyuki; Tanaka, Hidekazu; Motoji, Yoshiki; Mukai, Jun; Suto, Makiko; Takada, Hiroki; Soga, Fumitaka; Hatani, Yutaka; Matsuzoe, Hiroki; Hatazawa, Keiko; Shimoura, Hiroyuki; Ooka, Junichi; et al.
Abstract : Objectives: Pulmonary hypertension (PH) is characterized by marked and sustained elevation of pulmonary vascular resistance and pulmonary artery pressure, and subsequent right‐sided heart failure. Right ventricular (RV) function and exercise capacity have been recognized as important prognostic factors for PH. Our aim was to investigate RV contractile reserve and exercise capacity during a leg‐positive pressure (LPP) maneuver. Methods: The study population comprised 43 PH patients and 17 normal controls. All patients underwent echocardiography at rest and during LPP stress. Exercise capacity was assessed by 6‐minute walk distance for PH patients. RV relative wall thickness was calculated from dividing by RV free wall thickness by basal RV linear dimensions at end‐diastole. RV function was calculated by averaging peak speckle‐tracking longitudinal strain from the RV free wall. RV contractile reserve was assessed as the difference in RV free wall strain at rest and during LPP stress. Changes in left ventricular stroke volume (ΔSV) during LPP stress were also calculated. Results: ΔSV and RV contractile reserve of PH patients were significantly lower than of controls (3.6 ± 6.0 mL vs 8.5 ± 2.3 mL, and 8.2 ± 11.9% vs 14.5 ± 6.6%; both P  < 0.01). RV contractile reserve of PH patients with ΔSV <3.3 mL was significantly lower than of PH patients with ΔSV >3.3 mL (3.9 ± 13.2% vs 12.3 ± 8.9%; P  = 0.02). ΔSV had also significant correlation with 6‐minute walk distance ( r  = 0.42, P  = 0.006). Multivariate regression analysis showed that RV relative wall thickness was an independent determinant parameter of ΔSV during LPP stress for PH patients ( β  = 3.2, P  = 0.003). Conclusions: Preload stress echocardiography in response to LPP maneuver, a noninvasive and easy‐to‐use procedure for routine clinical use, proved to be useful for the assessment of RV contractile reserve and exercise capacity of PH patients.